Methods for enrichment of novel electrochemically-active microorganisms - Doyle, Lucinda Elizabeth; Marsili, Enrico (Bioresource technology, 2015)
•Current methods for EAM enrichment have uncovered only a small part of EAM diversity.•Potentiostat-controlled electrochemical cells provide higher repeatability than MFC-based enrichment.•Microbial-rich environments like sediments and soil are preferable to wastewater as inocula for EAM enrichment. Electrochemically-active microorganisms (EAM) are relevant to metal biogeochemistry and have applications in microbial fuel cells (MFCs), bioremediation, and bioelectrocatalysis. Most research conducted to date focuses on EAM hailing from two distinct genera, namely Shewanella and Geobacter, with a relatively limited number of EAM discovered in recent years. This review article summarises current approaches to novel EAM enrichment, in terms of inoculum choice, growth medium, reactor configuration, electrochemical characterisation and community profiling through metagenomics and metatranscriptomics. A novel roadmap for EAM enrichment and subsequent characterisation using environmental samples as a starting material is provided in order to increase throughput and hence the likelihood of discovering novel EAM.